Pyrotinib-assisted whole brain radiotherapy alleviates HER2-positive advanced breast cancer and brain metastases: a prospective study in patients - Zhou, Fulin; Zhang, Cui; He, Mingyuan; Ren, Yu; Yue, Hongshuang; Tan, Zhihua; Zhang, Shaolin; Li, Yong; Liu, Shu (Frontiers in Neurology, 2025)
PurposeThe whole-brain radiotherapy (WRBT)-based therapeutic efficacy is often limited against human epidermal growth factor receptor 2 (HER2+)-positive advanced breast cancer (BC) and brain metastases (BM), requiring more effective treatment options. This prospective study evaluates the effectiveness and safety of combining WBRT with pyrotinib in patients with HER2+ advanced BC and BM.MethodsThe enrolled patients (n = 26, from April 2019 to March 2022) were divided into two treatment groups. Group 1 (p-WBRT) received pyrotinib initially, followed by subsequent WBRT. Group 2 (WBRT-p) received WBRT concurrently with pyrotinib. The intracranial progression-free survival (iPFS) was determined.ResultsIn the WBRT-p group (n = 11), the median iPFS was recorded as 25.0 months (95% CI, 15.3–34.7), while the overall survival (OS) rates in 1–4 years were 100, 54.5, 9.1, and 0%, respectively. The intracranial objective response rate (iORR) and intracranial clinical benefit rate (iCBR) were 63.6 and 90.9%, respectively. In the p-WBRT group (n = 15), the median iPFS was around 22.0 months (95% CI, 4.3–39.7), and the OS rates in 1–4 years were 100, 53.3, 33.3, and 6.7%, respectively. The iORR and iCBR values were 66.7 and 80.0%, respectively. Notably, no significant differences in iPFS, OS, iORR, and iCBR were observed between treatment groups. Although some instances of adverse events, such as vomiting and reduced white blood cells and neutrophil counts, were evident, these adverse events were grades 1–3.ConclusionWBRT combined with pyrotinib exhibited exceptional tolerability, showing long iPFS in patients with HER2+ advanced BC and BM.